A global framework for climate mitigation policies: A technical contribution to the discussion on carbon pricing and equivalent policies in open economies - Eddy Bekkers; Ayse Nihal Yilmaz; Marc Bacchetta; Mateo Ferrero; Kirti Jhunjhunwala; Jeanne Métivier; Bright E. Okogu; Daniel Ramos; Enxhi Tresa; Ankai Xu (World Trade Organization (WTO), 2024)
We explore a global carbon pricing framework to inform the potential coordination of carbon pricing and equivalent policies. The framework has three main features aligning with the current multilateral system for climate action. First, the carbon price is determined by a global average carbon price to achieve emission reductions required to remain on a 1.5-2 degrees Celsius global warming trajectory. The framework further incorporates a set of economy-level criteria determining variation in carbon prices between economies: historical emissions, the current level of economic development, and the economic costs of climate change. Second, a moderate share of carbon pricing revenues is allocated to support lower-income economies, economies with higher costs of climate change and economies with higher economic costs of carbon pricing. Third, the framework allows economies to achieve equivalent carbon emission reductions through the implementation of alternative policy instruments. Simulations with the Global Trade Model show that, under the framework, the projected economic costs of carbon pricing are in proportion to the economy-level criteria, implying higher costs for economies with higher historical emissions, a higher level of development and lower projected costs of climate change. The projected reduction in output and exports in emission-intensive trade-exposed sectors (EITEs) displays only a weak negative correlation with the carbon price level. The framework is not meant as a policy proposal but as a contribution to the discussion on coordination of carbon pricing policies. Such coordination can help to inform the discussion about policy options to prevent fragmentation of carbon pricing and other climate change mitigation policies. Such fragmentation is costly and could lead to the introduction of complementary policies which could come with trade frictions.
Keywords: C68; F18; Q54; 330; Carbon pricing; Climate change mitigation; CGE Models